Measuring Household Resilience in the Climate Smart Villages in the Philippines, Myanmar and Cambodia - Edralin, Monica; Barbon, Wilson John; Cabriole, Marie Aislinn; Thant, Phyu Sin; Phen, Bunthoeun; Monville-Oro, Emilita; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
Resilience has traditionally been understood as a function of observable and measurable characteristics. More recently, discussions of household resilience have emphasized the need to pay attention to resilience as a set of capacities. What this paper aims to develop is a framework and a methodology for accounting both tangible and intangible characteristics found in the household, that is, measuring assets, social capital, as well as inherent personal characteristics or traits of the household decision-maker that may or may not predispose a household to be resilient. A framework from Béné (2014) was used as an analytical framework for both quantitative and qualitative studies. The quantitative study consists of surveying households (n=623) across six climate-smart villages (CSVs) in Myanmar, Cambodia, and the Philippines. Three dimensions of household resilience were identified: resilience capacities, subjective resilience, and intra-household gender relations. Each dimension of resilience is envisioned to complement the other in order to better understand household level resilience. The dimensions are consolidated in order to construct a Household Resilience Score (HRS). The study confirms that there are strong links found among relationships between the use of CSA initiatives and resilience capacities. The study also revealed that subjective resilience is equally important in understanding household resilience. There is a strong relationship in how households think they can recover from a shock in relation to specific psychosocial traits such as perseverance, self-efficacy, and conscientiousness.